2015
DOI: 10.1097/scs.0000000000001560
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Cleft Care

Abstract: Video teleconferencing can be used to provide comprehensive regional and international cleft care to facilitate initial evaluations and consistent follow-up. This technology can alleviate the travel burden on families and cleft care providers practicing over a large geographic radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews. 51 Specific objective clinical data were collected using text messages for daily surgical drain output, 55 electronic transmission of home spirometry results, 58 and more complex multi-modal monitoring of symptoms, blood pressure, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews. 51 Specific objective clinical data were collected using text messages for daily surgical drain output, 55 electronic transmission of home spirometry results, 58 and more complex multi-modal monitoring of symptoms, blood pressure, and medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…As stated by Pirris and coauthors, 56 the “absence of professional and legal guidelines regarding the safe use of mobile camera phones in a clinical setting may make formal adoption of the practice difficult and expose its users to medico-legal pitfalls.” Indeed, many of the studies included in this review used already-established technologies (eg Skype, online videoconferencing platforms, SMS text messaging, etc), with no modifications to make them compliant with HIPAA or otherwise ensure patient privacy and protection. Only 1 study 53 was explicit in using a HIPAA-compliant videoconferencing platform. In a review of the 10 most commonly used voice over internet protocol (VOIP) videoconferencing software, Watzlaf and associates 69 found frequent and widespread security vulnerabilities in nearly every platform studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have demonstrated the efficacy of telehealth in cleft care, and our experience here shows that interdisciplinary craniofacial care can be delivered virtually. 6 , 7 This experience has led us to re-envision how ideal craniofacial clinics will be structured in the future. In our experience, many evaluations can be accomplished over video, especially annual follow-up visits unlikely to require major intervention.…”
Section: Future Considerations For Craniofacial Carementioning
confidence: 99%